(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
This paper presents certain qualitative results of a pilot study concerning the development and evaluation of a teaching strategy based on the construction of a precursor model in developing understanding of the concept of the rolling friction in children of 5 years of age. The aim of this study was to explore the extent to which nature and the characteristics of a teaching intervention can bring about cognitive progress in preschoolers with regard to the factors rolling friction depends on, when it is applied to an object that is freely rolling on a horizontal surface.